Deixis In Jakarta Post Article - adi, mohammad sofyan; Rahmat, Muhamad Bagus Iqbal (International Journal of English Education and Linguistics (IJoEEL), 2020)
The design of this research was descriptive qualitative research that aimed at describing, interpreting and explaining deixis in the newspaper article. The main instrument in this study the researcher himself in doing his analysis supported by using the documentary technique. The data that had been collected were analyzed by the researcher himself. After analyzing the data, then the researcher drew the conclusion about the types and the function of deixis in the sentences of the newspaper articles. Based on the discussion findings,Â  there were four types of deixis found in The Jakarta Post article, namely 19 person deixis, 29 spatial deixes , 59 time deixis, 55 discourse deixis. From the analysis, the most types of deixis found in Jakarta Post articles time deixis. Thus, it can be said that The Jakarta Post tends to use time deixis as the dominant type compound than another.